Prevalence of Covid-19 Associated Symptoms, Their Onset and Duration, and Variations Among Different Groups of Patients in Bangladesh - Amin, Md. Tanzilul; Hasan, Mahmud; Bhuiya, N. M. Mahmudul Alam (Frontiers in Public Health, 2021)
Objective: This study aimed to assess the prevalence, onset, and duration of COVID-19 associated symptoms, hospitalization, and recovery time from the infection in Bangladesh. Methods: A retrospective study was designed adopting the snowball sampling technique (n=439). The association of gender, age, and comorbidity on COVID-19 associated complications was determined using chi-square and binary logistic regression analysis (p<0.05). Result: Fever, exhaustion, cough, loss of taste, sore throat, body ache, and hair-loss were prevalent among more than 50% of the participants and developed within fourth days in above 90% of the patients. Shortness of breath was significantly higher in males (χ2= 5.671; OR 1.641). Significant comorbidity association on the shortness of breath (χ2= 40.119; OR 2.564), vomiting (χ2= 4.422; OR 1.018), and loss of speech (χ2= 17.299; OR 3.430) was observed. Patients (>40 years) exerted higher association in shortness of breath (χ2= 24.083; OR 2.901). Age and comorbidity were significantly associated with COVID-19 associated hospitalization (χ2= 16.890 and χ2= 23.638, respectively) and recovery time (χ2= 12.870 and χ2= 26.924, respectively). Conclusion: The study suggests that the hospitalization rate increased for older (>40 years) and comorbid patients. Comorbid patients demonstrated higher susceptibility to have shortness of breath, vomiting, loss of speech, and confusion, whereas male patients showed significant increase in the prevalence of sore throat, loss of smell, and vomiting compared to female patients.